‘I am surrounded by people who are not motivated to do research’: harnessing collegiality for developing research active academics in a teaching-focused institution - Jeyaraj, Joanna Joseph; Wald, Navé (Taylor & Francis Online, 2023)
In order to achieve a university status, a teaching-focused private Malaysian University College promoted collaboration as an institution-wide strategy for developing the research capacity of staff. Enhancing collegiality was key to this strategy since resources for building research capacity were insufficient. Limited research exists on the role of collegiality in developing research capacities among academics, especially in the Global South and under such constraints. In Malaysia, a high-power distance country, difficulties arise in the practice of collegiality due to hierarchy and other socio-cultural expectations. In this qualitative study, insights into and experiences of this transition were sought in interviews with 18 academics. Collegial leadership and intellectual collegiality were identified as pivotal. Collegial leadership, which addressed the relationship between academics and institutional leaders, was lacking and participants mostly felt unsupported and disengaged under the dominant top-down, hierarchical, leadership style. Intellectual collegiality, which refers to the relationships participants had or wished to have with colleagues, was also challenging in that environment but held more promise. Actively promoting this through a process of assimilation and compromise could have been prioritised. Achievable and tangible research targets could have been negotiated so that becoming research active was a shared vision.